Injury rate and patterns of Sydney grade cricketers: a prospective study of injuries in 408 cricketers. Issue 1114 (26th July 2018) - Soomro, Najeebullah; Redrup, Daniel; Evens, Chris; Strasiotto, Luke Pieter; Singh, Shekhar; Lyle, David; Singh, Himalaya; Ferdinands, Rene E D; Sanders, Ross
Abstract: Background: The grade cricket competition, also known as premier cricket, supplies players to the state and national teams in Australia. The players involved are generally high-performing amateur (subelite) club cricketers. However, to date, there is no study on the injury epidemiology of Australian grade cricket. Aim: To conduct injury surveillance across all teams playing Sydney Grade Cricket (SGC) competition during the 2015–2016 season. Methods: A cohort study was conducted to track injuries in 408 male cricketers in 20 teams playing SGC competition. Players were tracked through the MyCricket website's scorebook every week. Cricket New South Wales physiotherapists were alerted if there were changes to the playing XI from the last game. If any changes were made due to injury, then an injury incident was registered. Results: During the course of the season, a total of 86 injuries were registered from 65 players, resulting in a loss of 385 weeks of play. The overall injury incidence rate was 35.54 injuries/10 000 playing hours with an average weekly injury prevalence of 4.06%. Lower back injuries (20%) were the most common injuries followed by foot (14%), hand (13.75%), knee (7.5%) and calf (7.5%). Linear regression analysis showed that the likelihood of injury increased as the mean age of the teams increased (R=0.5, p<0.05). Conclusion: The injury rate in SGC is lower than that reported at elite level. However, the high rate of lower back injuries (20%) highlights an area of concern in this cohort. High workloads or inadequate physical conditioning may contribute to such injuries. This study sets the foundation for understanding injury epidemiology in grade cricket and examines the links between injury and performance, these results may assist coaches and administrators to develop and implement cricket-specific injury prevention programmes.